1994
DOI: 10.2136/sssaj1994.03615995005800030025x
|View full text |Cite
|
Sign up to set email alerts
|

Water Content Effect on Denitrification and Ammonia Volatilization in Poultry Litter

Abstract: Poultry litter is a mixture of excreta, bedding material, waste feed, and some soil that is removed from poultry houses and applied to soil as fertilizer. Because litter is commonly stockpiled outdoors before land application, losses of inorganic N may occur through denitrification and NH3 volatilization. This work was conducted to evaluate the effect of litter water content on denitrification and NH3 volatilization during storage. Litter samples from two broiler houses in northern Georgia were incubated (25°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 0 publications
2
32
0
3
Order By: Relevance
“…It was comparable with N fertilization in Valencian Community region areas with intensive agricultural production in Spain, in which nitrogen fertilization in pepper and tomato cropping system could reach to 1030 and 940 kg N ha À1 , respectively (Ramos et al, 2002). Fertilizer N use efficiency in intensively managed greenhouse vegetable systems can be less than 10% using conventional management practices (Zhu et al, 2005), consequently large amounts of unused nitrogen are released to the environment through nitrate leaching, denitrification and NH 3 volatilization (Cabrera et al, 1993;Cabrera and Chiang, 1994;Fox et al, 1996;Gollany et al, 2004;Ramos et al, 2002). For example, nitrate-N concentrations in shallow wells around greenhouses in Huimin, Shandong, ranged from 9 to 274 mg N L À1 , with 99% of surveyed wells exceeding the USEPA limit of 10 mg N L À1 , more than half of the samples (53%) exceeding 50 mg N L À1 , and 26% exceeding 100 mg N L À1 (Ju et al, 2006).…”
Section: Introductionmentioning
confidence: 67%
“…It was comparable with N fertilization in Valencian Community region areas with intensive agricultural production in Spain, in which nitrogen fertilization in pepper and tomato cropping system could reach to 1030 and 940 kg N ha À1 , respectively (Ramos et al, 2002). Fertilizer N use efficiency in intensively managed greenhouse vegetable systems can be less than 10% using conventional management practices (Zhu et al, 2005), consequently large amounts of unused nitrogen are released to the environment through nitrate leaching, denitrification and NH 3 volatilization (Cabrera et al, 1993;Cabrera and Chiang, 1994;Fox et al, 1996;Gollany et al, 2004;Ramos et al, 2002). For example, nitrate-N concentrations in shallow wells around greenhouses in Huimin, Shandong, ranged from 9 to 274 mg N L À1 , with 99% of surveyed wells exceeding the USEPA limit of 10 mg N L À1 , more than half of the samples (53%) exceeding 50 mg N L À1 , and 26% exceeding 100 mg N L À1 (Ju et al, 2006).…”
Section: Introductionmentioning
confidence: 67%
“…Consequently, very high proportions of unused nutrients accumulate in the soil, and N is released into the environment through nitrate leaching, denitrification and NH 3 volatilization (Cabrera and Chiang 1994;Fox et al 1996;Gollany et al 2004;He et al 2007;Ramos et al 2002). Double cropping systems with two vegetable crops per year are widespread in northern China using unheated greenhouses constructed with a clay or brick wall with bamboo supports attached that are covered with polyethylene film.…”
Section: Introductionmentioning
confidence: 99%
“…De Bertoldi et al [31] suggested that the optimum pH values for composting are between 5.5 and 8.0. All piles except pile C were within the optimum range [33,34].…”
Section: Discussionmentioning
confidence: 95%